(untitled) (e-Journal of Linguistics, 2019)
This study investigated English-Indonesian translation of existential sentence. It aimed at (1) Identifying the way of translating English existential sentences into Indonesian and (2) Investigating kinds of translation shift found in the translation of English existential sentences into Indonesian. Existential sentence is a non-canonical sentence used to express the existence of something or someone marked by dummy subject there and copula be. Here, the English existential sentences were translated into the inversion structure in Indonesian with V-NP word order. The structure preserved the existential content by placing Indonesian existential verbs in the initial position of the sentences, there were two most frequently used verbs, those are ada and terdapat. Both verbs can be substituted to present the same ideas. Since English and Indonesian have different language structure, translation shift in term of structure shift was found in translating existential sentences from English into Indonesian.